The quantification of acceleration events in elite team sport: a systematic review - Delves, R. I. M.; Aughey, R. J.; Ball, K.; Duthie, G. M. (Sports Medicine - Open, 2021)
Background Wearable tracking devices are commonly utilised to quantify the external acceleration load of team sport athletes during training and competition. The ability to accelerate is an important attribute for athletes in many team sports. However, there are many different acceleration metrics that exist in team sport research. This review aimed to provide researchers and practitioners with a clear reporting framework on acceleration variables by outlining the different metrics and calculation processes that have been adopted to quantify acceleration loads in team sport research.